Antecedents and role of individual sociability on participation in mobile collaborative consumption. Issue 5 (4th April 2019) - Zhang, Yicheng; Phang, Chee Wei; Gu, Rui; Zhang, Chenghong
Abstract : Purpose: The purpose of this paper is to investigate what may influence participation in mobile collaborative consumption (CC). In particular, the authors investigate the effects of individual sociability and psychological antecedents including enjoyment, social connection, altruistic motivation, reputation, trust and embarrassment on the participation intention in this emerging phenomenon, as well as their relationships. Design/methodology/approach: Survey approach was employed to validate the research model. Findings: Hedonic factor, i.e. enjoyment, and social-related factors including altruistic motivation, reputation and embarrassment emerge as important antecedents of participation in mobile CC. On top of these factors, individual sociability plays an important role, by acting as a direct antecedent of the dependent variable, while also influencing their perceived greater altruistic motivation and reputation from participating in the CC. Yet, sociability has no significant effect on perceived enjoyment and embarrassment associated with the activity, suggesting that addressing these factors may encourage individuals with low sociability to participate. Originality/value: This study taps into mobile technology to support CC in daily consumption activities, and highlights the factors that influence people's participation in such activities. More importantly, the findings suggest that while it is more likely for individuals with high sociability to participate in this emerging form of social activities, for consumers with low sociability, addressing the enjoyment aspect and embarrassment issue of the activities may nonetheless promote their participation.